Primary School Children’s Practices of Watching Cartoons and Their Perceptions About Cartoon Character - İlhan, Vahit and Sacide Şahin (European Journal of Multidisciplinary Studies, 2017)
Relation between television and children is, to a large extend, associated through cartoons. Cartoons are in the leading preferential position of children audience from pre-school period to adolescence. Having been accessible all through 24 hours after the appearance of thematic children channels, cartoons have been opening doors of hundreds of various worlds. Stories, designed within the framework of global or domestic codes, are transmitting their messages through characters at first place. This research on audience was performed in Kayseri and is aimed to define the children’s habits of watching TV and cartoon and their perceptions about cartoon characters. A survey has been applied to 420 student from various age groups in 3 different schools ensampling three different socio-economic levels. According to the results gained, the most watched cartoon TV by primary school children is TRT Çocuk, most watched cartoon is Rafadan Tayfa and Kelo?lan is the most loved character among 96 different cartoon characters. It was determined that national productions are in the forefront but generally the international productions dominate. It was also determined that children define the behaviors of cartoon characters with adjectives such as good, nice...etc. Otherwise the characters have extraordinary features appears to be a factor which causes increase in the ratings. Moreover, it is suggested in the research that gender is an important determinant within the context of cartoon selection and adoption of cartoon characters.